ANALISIS YURIDIS TERDAHAP PEMBATALAN PENCABUTAN IZIN MENDIRIKAN BANGUNAN (STUDI KASUS PUTUSAN NO. 30/B/2012/PT.TUN.MDN) - Misalina Br. Bukit; Pendastaren Tarigan; Jusmadi Sikumbang; Edy Ikhsan (Universitas Sumatera Utara, 2016)
ABSTRACT IMB (Building permit) given by Regent and was revoked by the Regent of Deli Serdang District. The Ruling of TUN (State Administrative Court) which was not based on the principle of good governance, the principle of legal certainty and prudence as it is found in the Ruling No. 30/B/2012/PT.TUN.MDN) which harmed the IMB owners and was not in line with the regulation on IMB itself. This Ruling is highly needed to be analyzed. The result of the research showed that judge’s legal consideration which revoked IMB is actually the picture of TUN officials. Their rulings should be in line with the principle of good governance and supported by the fact that IMB owners has complied with the rule in which breaking down a building should be in line with the instruction so that the Ruling of TUN on the revocation of IMB was not correct. It is recommended that judge’s verdict should contain compensation so that it will cause intimidated effect. The TUN officials should be careful and pay attention to the principle of good governance, especially the principle of legal certainty and prudence in giving a ruling of TUN. Keywords: Revocation of Building Permit